1998
DOI: 10.1006/viro.1998.9104
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Cells and Neutralizing Antibodies Induced in Rhesus Monkeys by Virus-like Particle HIV Vaccines in the Absence of Protection from SHIV Infection

Abstract: HIV Pr55gag has in the absence of other viral components the capacity to self assemble in budding noninfectious virus-like particles (VLP). The immunological spectrum of the HIV-1IIIB gag-derived VLP was expanded either by stable anchoring of chimeric modified gp 120 on the surface of the VLP (type 1) or by replacing sequences of the Pr55gag precursor by the V3 loop and a linear portion of the CD4 binding domain (type 2). This noninfectious antigen delivery system was evaluated for immunogenicity and efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…It has been shown in previous studies that HIV Pr55 gag is a potent inductor of a CD8 ϩ CTL response (12,59). Therefore, we examined whether the generated mutant EHV-1 viruses were able to induce such a response.…”
Section: Pr55mentioning
confidence: 97%
“…It has been shown in previous studies that HIV Pr55 gag is a potent inductor of a CD8 ϩ CTL response (12,59). Therefore, we examined whether the generated mutant EHV-1 viruses were able to induce such a response.…”
Section: Pr55mentioning
confidence: 97%
“…This fact underscores the urgent need for an effective AIDS vaccine. Despite vigorous research efforts, preventive (sterilizing) immunization based on raising neutralizing Abs against HIV components has proved fruitless (1)(2)(3). In contrast, it is known that the host CTL responses provide powerful defense to contain the virus postinfection (4,5), and CTL-based immunization is currently the most promising approach toward vaccine development (6).…”
mentioning
confidence: 99%
“…As a step toward delineating the molecular basis of CTL escape, we undertook structural studies to reveal how Mamu-A*01 binds these two very different SIV peptides for presentation to the TCR. Previously, several studies have probed the interactions and structures of peptide and class I MHC molecules (pMHC) 3 from human and mice (34 -38). This is the first nonhuman primate pMHC structure ever solved, and the results show that the nonamer and octamer peptides bind to the Mamu-A*01 in a similar way with P3 as an anchor residue.…”
mentioning
confidence: 99%
“…VLPs resemble viral capsids morphologically and antigenically, and VLPs derived from a broad range of viruses have been shown to be immunogenic (5,10,14,15,21,28,29,32,35,41,45,50,52,59,60). VLPs are appealing as vaccine candidates because antigen is delivered in a noninfectious form in the absence of viral genome or other potentially toxic viral gene products.…”
mentioning
confidence: 99%
“…This lipid envelope may contain hostderived proteins (18,43,57). Immunogenicity studies involving HIV-1 Gag VLPs have been carried out with particles derived from insect cells infected with recombinant baculovirus vectors (45,59). These studies demonstrated that HIV-1 Gag-specific immune responses can be generated by parenteral administration of Gag VLPs, even without the coadministration of adjuvants.…”
mentioning
confidence: 99%